Evaluation of physical, structural properties and shielding parameters for K2O-WO3-TeO2 glasses for gamma ray shielding applications - Ersundu, M. Celikbilek; Ersundu, A. E.; Sayyed, M. I.; Lakshminarayana, G.; Aydin, S. (ELSEVIER SCIENCE SA, 2017)
In the present work, a series of ternary glasses in the K2O-WO3-TeO2 system have been synthesized by conventional melt quenching technique. Glass formation range of the selected glass system was determined and physical, structural and radiation shielding properties of the glasses were investigated. Density (rho), molar volume (V-M), oxygen molar volume (V-O), oxygen packing density (OPD), average crosslink density ((n) over bar ((c) over bar)), the number of bonds per unit volume (n(b)) and Poisson's ratio (mu(cal)) values were evaluated for the interpretation of physical and structural properties. Fourier transform infrared (FTIR) spectra of the glasses were analyzed in order to obtain the information on the structural transformations in the glass network following the equimolar substitution of TeO2 by K2O + WO3 and changing K2O or WO3 at constant TeO2. Increasing K2O at constant TeO2 decreases the network connectivity due to the formation of non-bridging oxygen sites and the glass network became less tightly packed. On the other hand, equimolar substitution of TeO2 with WO3+K2O in these glasses resulted in a more compact glass network. The mass attenuation coefficients have been computed using WinXCom program and the obtained values were used to calculate the half value layer, the effective atomic number and the electron density. In addition, the macroscopic effective removal cross-section for fast neutron values are also evaluated. The variation of shielding parameters was discussed for WO3 variation in the glass composition and photon energy. From the derived results, it was found that K30W60T10 is the best glass in terms of shielding effectiveness among all the studied glasses due to higher values for mass attenuation coefficient, effective atomic number, and electron density and lower values of half value layer. These glasses show potentiality to be used as shielding materials and for an improved shielding effectiveness of the K2O-WO3-TeO2 glasses, a large WO3 content would be required. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Optical materials; Tellurite glasses; Fourier transform infrared spectroscopy; Mass attenuation coefficients; Half value layers; Macroscopic effective removal cross-section; EFFECTIVE ATOMIC-NUMBER; DIFFERENT OXIDE COMPOSITIONS; ATTENUATION COEFFICIENTS; RADIATION; SYSTEM; PB; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering